(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was carried out using seven varieties of jute, two varieties of kenaf and one variety of mesta to evaluate their germination potential to chromium (Cr) toxicity. Percent germination and primary growth parameters of these varieties in Cr contaminated medium were observed. Six levels (0, 20, 40, 80, 120 and 160 mg Cr L-1) of Cr were applied in artificial germinating medium following CRD with three replication. All the jute, kenaf and mesta varieties showed decreasing trend of germination with increasing levels of Cr. Germination of kenaf (HC-95 and HC-3), mesta (Samu-93) and jute (CVE-3 and BJC-7370) were satisfactory levels up to 160 mgCr L-1. The root and shoot lengths and fresh and dry weights also reduced with increased concentrations of Cr as the toxic effect of Cr retards the growth of meristematic tissues of young roots and shoots. Morphological deformities like twisting, curling of leaves and shoot and rottening of roots appeared at high concentrations of Cr. Due to receiving higher concentrations of Cr the color of the roots became dark brown to black. The potentiality of the varieties to Cr toxicity were kenaf HC-95 > kenaf HC-3 > mesta Samu-93 > jute CVE-3 and > jute BJC- 7370. The findings of the present study can be applied for sowing kenaf, mesta and jute seeds in Cr contaminated soil. J. Environ. Sci. & Natural Resources, 8(1): 51-57 2015